2020
DOI: 10.31557/apjcp.2020.21.11.3285
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Sarcopenia is Associated with Lack of Response to Therapy, Liver Decompensation and High Mortality in Hepatocellular Carcinoma Patients

Abstract: Objective: hepatocellular carcinoma (HCC) is a dreadful complication of liver cirrhosis. Aim was to study the effect of sarcopenia on the survival in patients with HCC. Methods: we included 262 patients and were followed up for 12 months. Sarcopenia was calculated by skeletal muscle index (SMI). Sarcopenia was defined by SMI ≤39 cm 2 /m 2 for women and ≤50 cm 2 /m 2 for men. Results: patients with sarcopenia (n= 113, 43.1%) were older, mainly males, Child-Pugh class B and smokers. Patients with sarcopenia had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
(29 reference statements)
0
9
0
3
Order By: Relevance
“…Moreover, elevated IL-6 and decreased IL-15 in pre-cachetic and cachetic patients can alter the function of immune cells, which resulted reduced anti-tumor effect 35 . Notably, patients with baseline sarcopenia compared to those without, had significant higher percentage of progressive HCC despite intervention in the 1st (29.2 vs. 16.1; p = 0.023), 3rd (40.7 vs. 29.5; p = 0.001), 6th (51.4 vs. 30.6; p = 0.001) and the 12th months (32.1 vs. 25.7; p = 0.001) 36 . One previous study reported that sorafenib responses are diminished in individuals with sarcopenic obesity with increased visceral fat, which suggests body composition could be predictive marker for primary resistance to tyrosine kinase inhibitors in patients with advanced HCC 37 .…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, elevated IL-6 and decreased IL-15 in pre-cachetic and cachetic patients can alter the function of immune cells, which resulted reduced anti-tumor effect 35 . Notably, patients with baseline sarcopenia compared to those without, had significant higher percentage of progressive HCC despite intervention in the 1st (29.2 vs. 16.1; p = 0.023), 3rd (40.7 vs. 29.5; p = 0.001), 6th (51.4 vs. 30.6; p = 0.001) and the 12th months (32.1 vs. 25.7; p = 0.001) 36 . One previous study reported that sorafenib responses are diminished in individuals with sarcopenic obesity with increased visceral fat, which suggests body composition could be predictive marker for primary resistance to tyrosine kinase inhibitors in patients with advanced HCC 37 .…”
Section: Discussionmentioning
confidence: 94%
“…Multiple studies have reported outcomes among these patients. It has been showed that a baseline sarcopenia is associated with lack of response to HCC treatments, further decompensation episodes, and increased mortality[ 56 ]. In the following sections, we elaborate on studies evaluating the role of sarcopenia in HCC patients with various treatments such as loco-regional, surgery, transplant, and chemo/immunotherapy.…”
Section: Changes In Sarcopenia With Hcc Treatmentsmentioning
confidence: 99%
“…In der aktuellen ESPEN-Leitlinie "Klinische Ernährung bei Lebererkrankungen" wird zur Bestimmung der Mangelernährung der Nutritional-Risk-Score (NRS 2002) oder Minimal Nutrition Assessment (MUST) oder The Royal Free Hospital Nutrition Prioritizing Tool (RFH-NPT) empfohlen. Sarkopenie bei Patienten mit HCC ist mit schlechter Therapieverträglichkeit sowie erhöhter Mortalität assoziiert [390][391][392][393][394]. Geringe Handkraftstärke und niedriger Phasenwinkel alpha (gemessen mit der Body-Impedance-Analyse) können Auskunft über ein erhöhtes Mortalitätsrisiko geben [395].…”
Section: Leitlinieunclassified